2022
DOI: 10.3390/ijerph191710866
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Multiple Family Factors Associated with Oppositional Defiant Disorder

Abstract: Oppositional Defiant Disorder (ODD) is characterized by a recurrent pattern of angry/irritable emotional lability, argumentative/defiant behavior, and vindictiveness. Previous studies indicated that ODD typically might originate within a maladaptive family environment, or was at least maintained within such an environment. As such, the present review summarized pertinent research from the last 20 years that focused on the pathways connecting family risk factors to the development of child ODD symptoms. A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 105 publications
0
7
0
1
Order By: Relevance
“…Previous research has suggested that there may be a causal link between PCR and ODD symptoms [11]. However, the causal inference based on SEM or RCT-based intervention studies is quite limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has suggested that there may be a causal link between PCR and ODD symptoms [11]. However, the causal inference based on SEM or RCT-based intervention studies is quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline ODD and FACES were the most two important and used as the root node and secondary node respectively in the representative tree. The multilevel family model has proposed that factors at the entire family level play a basic supporting function in the family system, and are distal factors to affect ODD symptoms indirectly via more proximal factors, such as PCR and child emotion regulation [11]. When ODD children have more emotional and behavioral problems, there are more likely to be con icts with their parents [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the high prevalence of ODD and its long-term adverse consequences, it is essential to study the development of ODD among school-age children, as well as its precursors and consequences. Among the many factors related to ODD symptoms, it has been suggested children’s emotion regulation is critical [ 8 , 9 ]. However, recent theorists have proposed that emotion regulation is a dynamic process, and the intraindividual dynamics of emotion regulation is different among individuals, while there is also a two-way interaction between emotion regulation and behavior [ 10 ].…”
Section: Introductionmentioning
confidence: 99%